Analysis of Lean Six Sigma Modeling in Efforts to Improve Operational Performance at Royal Surabaya Hospital - Pasaribu, Betsy Tiurma; Mujanah, Siti; Fianto, Achmad Yanu Alif (International Journal of Economics (IJEC), 2025)
This study analyzes the implementation of the Lean Six Sigma model in an effort to improve operational performance at Royal Surabaya Hospital, considering the importance of efficiency and quality in modern healthcare. This study is a descriptive qualitative study that comprehensively examines the implementation process, barriers and challenges, and the impact of this methodology on the organization. Data were collected through in-depth interviews, participant observation, and document review from February to April 2025. The study findings indicate that the implementation of Lean Six Sigma significantly improved operational efficiency. Patient registration time was reduced by 25% (from 15 minutes to 11 minutes), waiting time for drug dispensing was reduced by 20% (from 20 minutes to 16 minutes), operational costs were reduced by 15%, and patient satisfaction increased by 30%. Implementation challenges included resistance from staff, limited training resources, and inadequate management commitment. This study provides empirical evidence on the effectiveness of Lean Six Sigma in private hospitals in Indonesia, as well as providing several recommendations for sustaining the program.